2016
DOI: 10.3329/jsr.v8i2.26867
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topography and Soil Depth on Clay Content, Organic Matter Content, Active Acidity, Reserve Acidity and Cation Exchange Capacity of Some Tea Soils of Bangladesh

Abstract: Soil samples were collected from M. R. Khan tea-estate area of Moulvibazar district, Bangladesh. Organic matter, active acidity, reserve acidity, cation exchange capacity, clay content and textural class of the collected soil samples for different topographic positions and depths were determined. The percentage of sand, silt and clay varied from 59.75 to 70.50, 12.50 to 20.00 and 14.50 to 22.75, respectively. Active acidity and reserve acidity of the soils varied from 4.13 to 5.82 and 3.46 to 4.84, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…This depth (60-90 cm) is known to contain higher clay content. Consequently, there was an increase in the percentage of clay content with the increase in depth of the subsoil horizon, and the same result was reported by [35]. This study suggested that greater clay content with depth is the most likely reason for the higher Bd in the subsoil.…”
Section: Effect Of Soil Depth and Land Cover On Physiochemical Propersupporting
confidence: 76%
“…This depth (60-90 cm) is known to contain higher clay content. Consequently, there was an increase in the percentage of clay content with the increase in depth of the subsoil horizon, and the same result was reported by [35]. This study suggested that greater clay content with depth is the most likely reason for the higher Bd in the subsoil.…”
Section: Effect Of Soil Depth and Land Cover On Physiochemical Propersupporting
confidence: 76%
“…Although, both soils were not significantly different with respect to physical properties, but the lower concentrations in clay and silt in the topsoil compared to subsoil indicated the movement of the particles to the lower horizon. This was confirmed by Adugna and Abegaz [32] and Sanaullah et al [33] that many topmost soils contain a relatively low amount of silt and clay in the surface layer resulting from the downward movement of the particles with drainage/percolating waters.…”
Section: Discussionsupporting
confidence: 55%
“…Hossain et al [33] reported on a range of CEC of 5.15 to 33.25 meq/100g soil at Satgoan, Baraora and Kurmah tea estates, in Sylhet, Bangladesh. Additionally, CEC ranged from 11.42 to 24.86 meq/100 g soil of Moulvibazar district, Bangladesh [34]. This variation of CEC was accompanied with the amount of clay content, pH, and percentage of organic matter in the investigated soils [35].…”
Section: Fig 1 Location Of Sampling Sitesmentioning
confidence: 89%